Trichomycterus igobi, a new catfish species from the rio Iguaçu drainage: the largest head in Trichomycteridae (Siluriformes: Trichomycteridae). - (:unkn) unknown (Sociedade Brasileira de Ictiologia, 2008)
A new species of Trichomycterus is described for the rio Iguaçu drainage in Southern Brazil. Trichomycterus igobi, new species, is readily distinguishable from all other species currently in the genus by its extremely large head (23.8-26.8 % SL), which is proportionally the largest head in any Trichomycteridae. That characteristic plus the relatively deep body result in a very short-bodied overall aspect, the most extremely such case in the genus Trichomycterus. Other diagnostic features that distinguish the new species from most or all of its congeners include a short caudal peduncle (15.4-19.7 % SL); an almost entirely cartilaginous second hypobranchial (with only vestigial ossification); a mesial expanded palatine ossification; a narrow cleithrum, falciform in shape; and the lack of a proximal posterior concavity on the third ceratobranchial. The new species seems to form a monophyletic group with T. stawiarski and other undescribed species (T. sp. C), also endemic to the rio Iguaçu. As putative synapomorphies, the three species share a rigid spine-like morphology of individual procurrent caudalfin rays, an extended area of dorsal caudal-fin procurrent rays, and numerous branchiostegal rays (ten or eleven).
Keywords: Systematics; Taxonomy; Fishes; Trichomycterinae; Paraná - Brasil; Sistemática animal; Taxonomia animal